(untitled) (Journal of the College of Basic Education, 2026)
Research objectives: The current research aims to achieve the following: Constructing an educational design for the acquisition of decorative concepts. B - Identifying the effect of using an educational design on the achievement of decorative concepts among students of the Department of Art Education studg hypotheses. There are no statistically significant differences at level 5 between the scores of the experimental group who studied according to the educational design and the scores of the control group who studied according to the traditional method in the skill test. In the current research, the researcher adopted the experimental design because of its scientific importance in educational research, and it is the most appropriate for achieving the objectives and hypotheses of the research The research community included second-year morning study students, numbering 227 male and female students, distributed across 6 halls. The research sample was drawn randomly, with two classrooms, numbering 69, from Hall 1, which represented the experimental group, numbering 35, and the control group was represented by Hall 4, numbering 34 male and female students After analyzing the educational content of the Arabic Calligraphy and Islamic Ornamentation course, the term "geometric ornamentation" was identified, and focus was placed on some decorative concepts. The researcher formulated 15 behavioral objectives that were presented to a number of specialized experts to ensure their production and representation of the geometric ornamentation included in the experiment. After analyzing the educational content, the researcher prepared an educational unit of lessons designed according to the steps of educational design (skills analysis stage, education design and learning stage, production development stage, education implementation stage, education management stage, education evaluation stage). A multiple-choice cognitive test was prepared according to the behavioral objectives of the concepts identified within the research boundaries. The test consisted of (1) paragraph. A skill test was also prepared for the research sample consisting of (1) skill questions. This test was presented to a group of specialized experts The researcher used statistical messages according to the (SSPS) program to arrive at the results. The results demonstrate the superiority of the experimental group, which studied according to the educational design prepared for this presentation, over the control group, which studied according to the traditional method. In light of the results, the researcher recommends the following: Using an educational design to teach concept acquisition in the subject of Arabic calligraphy and Islamic ornamentation. Using educational programs and designs in the subject of teaching methods in the art education departments in the faculties of basic education and fine arts, fine arts institutes, and art schools. Paying attention to scientific seminars and workshops that focus on applying educational designs in lessons.Skills. Art. The effectiveness of using an educational design in the acquisition of concepts in the subject of Arabic calligraphy for students of the Department of Education.